Character Formation Through Farming Gardening Project at Attamam Elementary School - Dermawan, Oki; Busmayaril, Busmayaril; Irawansyah, Irawansyah; Jaya, Semar (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2021)
This research on character building of students through the farming gardening project aims to reveal: 1) Planning for school and community cooperation through farming gardening projects at SD Islam At Tamam 2) Implementation of school and community collaboration through farming gardening projects at SD Islam At Tamam 3 ) The impact of the farming gardening projects at SD Islam At Tamam is for the character building of students. This activity involves the principle of teaching staff, landowners, guardians of students and students. The implementation of the Farming Gardening project is led directly by the Principal of SD Islam At Tamam and is always accompanied by cultivating attitudes and morals, by continuing to maintain relationships between all parties involved. the impact on changes in the character of students in a more positive direction, such as collaboration, work hard, responsible, diligent, independent, sensitive to the environment, economic, entrepreneurial, sd become a benchmark for the success of farming gardening projects.Keywords: Farming Gardening, School and Community Collaboration